2012
DOI: 10.1016/j.fuel.2012.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyzed phthalocyanines as surrogate carbon catalysts: Initial insights into oxygen-transfer mechanisms

Abstract: a b s t r a c tDeposited and heat-treated phthalocyanines are promising electrocatalysts for replacing platinum in the oxygen reduction reaction (ORR), the most important process in energy conversion systems such as fuel cells; and yet its key mechanistic features are not well understood. To optimize their use, it is necessary to understand their behavior in the absence of an electric field. In the pursuit of this goal, we pyrolyzed metal-free, cobalt and copper phthalocyanines between 550 and 1000°C and studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 90 publications
(105 reference statements)
1
16
0
Order By: Relevance
“…Though the electrolysis conditions such as reaction phase, supporting electrolyte, pH value, etc., were very different from our conditions, it has been already reported that the Co–N 4 center in Co–TPP and Co–Pc was effective for the CO 2 reduction. 21 , 23 , 29 , 39 , 46 50 We have also reported that Co–phthalocyanine supported on a carbon support (vapor-grown carbon fiber, Showa Denko Co.) showed a lower electrocatalytic activity for the reduction of CO 2 to CO in the gas phase. 50 These facts proposed that a Co–N 4 structure was effective for the CO 2 reduction.…”
Section: Resultsmentioning
confidence: 88%
“…Though the electrolysis conditions such as reaction phase, supporting electrolyte, pH value, etc., were very different from our conditions, it has been already reported that the Co–N 4 center in Co–TPP and Co–Pc was effective for the CO 2 reduction. 21 , 23 , 29 , 39 , 46 50 We have also reported that Co–phthalocyanine supported on a carbon support (vapor-grown carbon fiber, Showa Denko Co.) showed a lower electrocatalytic activity for the reduction of CO 2 to CO in the gas phase. 50 These facts proposed that a Co–N 4 structure was effective for the CO 2 reduction.…”
Section: Resultsmentioning
confidence: 88%
“…Meanwhile, extensive investigation regarding carbon-oxygen gasification were carried out from which clear evidences about the involved active sites and the reaction mechanism were collected [21,22]. Oxygen-transfer reactions of carbon materials are at the heart of fuel combustion and gasification processes and much progress has been made in achieving their fundamental understanding [23]. As described by reaction (1), in carbon gasification or combustion the oxygen molecule reacts with the carbon reactive site (Cf1) from the carbon structure forming an intermediate that desorbs as CO or CO2.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports on the electrocatalytic properties of carbon materials modified with Co and Fe phthalocyanines and porphyrins and there is a continuously growing research activity in this area [37][38][39]. Whereas the ORR on Cu phthalocyanine (CuPc) and especially on Mn phthalocyanine (MnPc) modified carbon materials is rather poorly investigated compared to aforementioned other transition metal macrocyclic catalysts [21,34,[40][41][42][43][44][45][46][47]. MnPc-based catalysts may reportedly have similar electrochemical behaviour to that of Fe phthalocyanine [41].…”
Section: Introductionmentioning
confidence: 99%